Antimicrobial and Antioxidant Activity of Ants Nest Plant Extract (Hydnophytum formicarum Jack.) on The Growth of Test Microbials - Nurmiati, Nurmiati; Periadnadi, Periadnadi; Putra, Wahyu Dwisa; Syafrina, Vellin Putri (Jurnal Biologi Tropis, 2025)
Ant nest plants are epiphytic plants that contain active compounds that act as antimicrobials. This study aims to determine the antimicrobial and antioxidant activities of ant nest plant extracts, determine the Minimum Inhibitory Concentration (MIC) and Maximum Killing Concentration (MBC) of test microbes, determine the presence of polyphenols from several ant nest extracts. The method used in this study is the nested pattern experiment method. The results showed that dry brew extract + lime gave a significantly different effect on dry brew extract and dry boil against E. coli and S aureus, but did not give a significantly different effect on C. albicans. The MIC of dry brewed extract + lime against E. coli, S.aureus, and C. albicans is 3.12%, 1.5% and 25%, and is able to kill with an MIC of 6.25%, 3.12% , and 50%. The polyphenol value in the dry brewed extract + lime was 11.28 mgGAE/mL, the dry brewed extract was 9.94 mgGAE/mL, and the dry boiled extract was 4.13 mgGAE/mL. The antioxidant value of dry brewed extract + lime with an IC50 value of 78.14 μg/ml, dry brewed extract with an IC50 value of 98.68 μg/ml in the strong activity category and dry boiled extract with an IC50 value of 106.24 μg/ml in the medium activity category.